Digital Image Security System Using Spritz Algorithm - Mhd Furqan; Rakhmat Kurniawan; Abdul Halim Hasugian; Imam Zaki Husein Nst (INFOKUM, 2021)
Private and confidential digital imagery is particularly vulnerable to eavesdropping by irresponsible parties. Especially when distributed through the internet network such as on facebook chat-based applications, whatsapp and e-mail media. The image sent is sometimes often an image that is confidential and must be maintained security. In order to maintain the security of digital imagery can be done with the use of cryptographic techniques. Cryptographic techniques can secure digital images by changing the pixel values of the digital image so as to produce pixel values that are different from the original image to be secured. The research will use the Spritz algorithm for encryption and decryption of digital images in image security applications. The result of the Spritz Algorithm's encryption results in pixel values that are much different from the original pixel values. So that the image of encryption is more secure to be distributed through intermediary media.